Marketing strategy and competitive positioning - Hooley, Graham J.; Lee, Nick; Nicoulaud, Brigitte; Rudd, John M. (Pearson Education, 2020)
"Since the sixth edition of this book, published in 2017, many economies around the world have continued to feel the aftershocks of the deepest recession since the Great Depression of the 1930s, which started with the well-publicised 'credit crunch'. Despite continuing academic debate about the causes and extent, there is now little doubt that climate change and global warming is beginning to have a significant impact on our physical environment. Technology and the ever-growing acceptance and use of social media are having a profound effect on customer expectations, experience and behaviour. Despite ongoing economic difficulties and turbulence, climate change has not been ignored, and it presents significant challenges and opportunities for businesses. Sustainable energy technologies, such as wind, solar, wave and thermal biomass, are now being pursued more vigorously and attempts to reduce energy consumption (of cars, buildings and airplanes) are creating new business opportunities. Increasingly, companies, public sector organisations, individuals and nations are adopting and implementing measures, such as sourcing more raw materials locally to reduce 'carbon miles' and limiting the use of high-emission travel options to reduce their carbon footprint"--Provided by publisher